2020
DOI: 10.4047/jap.2020.12.5.322
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of conventional provisional resin to 3D printed resin: the role of surface treatments and type of repair resins

Abstract: PURPOSE This study evaluated the shear bond strength between 3D printed provisional resin and conventional provisional resin depending on type of conventional provisional resin and different surface treatments of 3D printed resin. MATERIALS AND METHODS Ninety-six disc-shaped specimens (Ø14 mm × 20 mm thickness) were printed with resin for 3D printing (Nextdent C&B, Vertex-Dental B. V., Soesterberg, Netherlands). After post-processing, the specimens were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…The group repaired with bisacrylic composite without any additional surface treatment showed the highest micro-shear value and the difference from all the other groups was statistically signi cant. It was also shown that additional mechanical or chemical surface treatments did not increase the shear bond strength in the repair groups of the two different materials [31]. These results aligned with the results of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…The group repaired with bisacrylic composite without any additional surface treatment showed the highest micro-shear value and the difference from all the other groups was statistically signi cant. It was also shown that additional mechanical or chemical surface treatments did not increase the shear bond strength in the repair groups of the two different materials [31]. These results aligned with the results of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Preliminary measurements with cleaned substrates and without mechanical pretreatment already showed insufficient bond strengths initially, especially centrifuging, and non-pretreated substrates achieved bond strength values of zero. An investigation regarding the repair of 3D-printed resin substrates resulted in the recommendation to repair the printed substrates with temporary composite resin without mechanical pretreatment, but the substrates were not chemically or physically cleaned [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alumina powder displayed especially promising results [ 13 ] but has been criticized for damaging the surface, whereas air-abrasion with glass pearls would be sufficient [ 14 ]. Only a few in vitro studies have been concerned with the influence of air-particle abrasion on the surface properties of 3D printable resin restorations [ 15 , 16 ]. None of them though takes air-abrasion pressure into account.…”
Section: Introductionmentioning
confidence: 99%
“…The highest bond strength was observed in the air abrasion group, and there was a significant difference. Lim and Shin 31 compared shear bond strength according to surface treatment to 3D-printed provisional resin with repair resin, composed of PMMA, as follows: no surface treatment, soaking in monomer, sandblasting with Al 2 O 3 (50 µm), and sandblasting with monomer application. All four groups exhibited no significant differences.…”
Section: Discussionmentioning
confidence: 99%